2000
DOI: 10.1038/sj.jhh.1001059
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in developing nations in sub-Saharan Africa

Abstract: There is a rapid development of the 'second wave epidemic' of cardiovascular disease that is now flowing through developing countries and the former socialist republics. It is now evident from WHO data that coronary heart disease and cerebrovascular disease are increasing so rapidly that they will rank No. 1 and No. 5 respectively as causes of global burden by the year 2020. In spite of the current low prevalence of hypertensive subjects in some countries, the total number of hypertensive subjects in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 50 publications
4
59
0
1
Order By: Relevance
“…Hypertension is a key driver of the cardiovascular disease (CVD) epidemic in Africa, and a major independent risk factor for heart failure, stroke and kidney failure [6,7]. A recent study conducted in Zimbabwe showed that the prevalence of uncontrolled hypertension was still high despite patients being treated with medication [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a key driver of the cardiovascular disease (CVD) epidemic in Africa, and a major independent risk factor for heart failure, stroke and kidney failure [6,7]. A recent study conducted in Zimbabwe showed that the prevalence of uncontrolled hypertension was still high despite patients being treated with medication [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other potential cause of heart failure like rheumatic heart disease (24) or myocarditis (presumably linked to infectious diseases like streptococcus and HIV infections (26,27) are frequent in SSA settings. However, the uncontrolled blood pressure remains the major factor for left ventricular hypertrophy (LVH) (28) and heart failure (29,30). The same holds for stroke (24,31,32) and renal failure (33)(34)(35).…”
Section: Differences In Risk From Hypertensionmentioning
confidence: 99%
“…1 Hypertension is a major public health concern in the urbanised black population in South Africa. [2][3][4] Adults in the South African North West Province are no exception, and indicated a hypertension rate of 21.8%. 5 Although clinical hypertension occurs less frequently in children than in adults, [6][7][8] ample evidence now supports the concept that the roots of essential hypertension extend back to childhood.…”
Section: Introductionmentioning
confidence: 99%